2015
DOI: 10.4253/wjge.v7.i6.652
|View full text |Cite
|
Sign up to set email alerts
|

Role of double-balloon enteroscopy in malignant small bowel tumors

Abstract: DBE may be critical in the management of MSBT providing additional information that may be decisive in the clinical course of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 34 publications
0
39
2
Order By: Relevance
“…The first-line treatment for small intestinal GISTs with excessive bleeding remains debatable (10,11). The endoscopic treatment by DBE is very limited in massive GIST bleeding, but it may be possible, delaying or averting emergency surgery (9). In the present case, DBE was unable to avert emergency surgery, but located the level of the bleeding and guided resection.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The first-line treatment for small intestinal GISTs with excessive bleeding remains debatable (10,11). The endoscopic treatment by DBE is very limited in massive GIST bleeding, but it may be possible, delaying or averting emergency surgery (9). In the present case, DBE was unable to avert emergency surgery, but located the level of the bleeding and guided resection.…”
Section: Discussionmentioning
confidence: 72%
“…The most common clinical indications of GISTs include obscure bleeding, abdominal pain, anemia, chronic diarrhea and inflammatory bowel disease (8). Robles et al (9) reported that the histological detection rate of GISTs by DBE biopsy was 71.4%. The first-line treatment for small intestinal GISTs with excessive bleeding remains debatable (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…According to the report, small bowel tumors included GIST (28.6% to 32.1%), adenocarcinomas (20.5% to 25%), neuroendocrine tumor (14.3% to 15.2%), malignant lymphomas (10.7% to 14.3%), adipose tumors (8.9%), metastatic tumors (10.7%), and Kaposi sarcoma (3.6%) [11,12] . Furthermore, the types of malignant small bowel tumor included adenocarcinoma (47%), carcinoid (28%), leiomyosarcoma (13%), and lymphoma (12%) [13] .…”
Section: Discussionmentioning
confidence: 99%
“…The most common SBTs are gastrointestinal stromal tumor (GIST), adenocarcinoma, NET, and lymphoma [79]. Overall, SBTs are more frequent in the jejunum, followed by the duodenum and ileum, and most present with SBB [80][81][82][83].…”
Section: Small Bowel Tumorsmentioning
confidence: 99%